Optimalisasi Pemanfaatan Nira Aren (Arenga pinnata Merr) di Dusun Ta'e Pindang Desa Alu Kabupaten Polewali Mandar - Karim, Faradilah Farid (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2024)
The potential of Ta'e Pindang Village, Polewali Mandar Regency in the agricultural aspect, especially sugar palm (Arenga pinnata Merr) is a superior product in its own region. The process of making palm sugar has been going on for a long time and has been practiced by people for generations. The problem that occurs is the lack of skills and knowledge, so that the community is still not optimal in utilizing the potential of sugar palm plants in their area. Until now, people in Ta'e Pindang village only use sugar palm plants by processing them into solid sugar and palm juice which is processed into palm wine. In fact, the products that can be produced from palm sap are very diverse, such as ant sugar, which in terms of selling price will be higher that solid sugar. Therefore, the aim of this PKM is to socialize to the people of Ta'e Pindang village about optimizing palm sap products into ant sugar with high economic value.  It is hoped that the results of the service activities carried out will increase people's insight and interest in utilizing palm sap into other products which in terms of economic benefits are more promising that the products that have been made so far.